Activating room-temperature phosphorescence of 1, 8-naphthalimide by doping into aromatic dicarboxylic acids. Issue 22 (25th February 2022) - Wang, Xiangming; Wang, Zepeng; Feng, Hua; Lin, Chongyang; Shi, Huifang; An, Zhongfu; Su, Zhong-Min; Liang, Fu-Shun
Abstract : The parent 1, 8-naphthalimide, which is otherwise room-temperature phosphorescence inert, was activated by doping into aromatic dicarboxylic acids, leading to efficient and long-lived phosphorescent emission. Abstract : The room-temperature phosphorescence of 1, 8-naphthalimide was activated by doping it into aromatic dicarboxylic acids. The doping system gives a bright yellow afterglow and 1, 8-naphthalimide and isophthalic acid (0.02 mol% doping content) afford a phosphorescent lifetime of 403 ms and a quantum yield of 4.2%. Both energy transfer from the host to the guest and the formation of an intermolecular hydrogen-bonding network are responsible for the observed efficient and long-lived phosphorescence.